HEK293 Cell Line as a Platform to Produce Recombinant Proteins and Viral Vectors - Tan, Evan; Chin, Cara Sze Hui; Lim, Zhi Feng Sherman; Ng, Say Kong (Frontiers in Bioengineering and Biotechnology, 2021)
Animal cell-based expression platforms enable the production of complex biomolecules such as recombinant proteins and viral vectors. Although most biotherapeutics are produced in animal cell lines, production in human cell lines is expanding. One important advantage of using human cell lines is the increased potential that the resulting biotherapeutics would carry more ‘human-like’ post-translational modifications. Among the human cell lines, HEK293 is widely utilized due to its high transfectivity, rapid growth rate, and ability to grow in a serum-free, suspension culture. In this review, we discuss the use of HEK293 cells and its subtypes in the production of biotherapeutics. We also compare their usage against other commonly used host cell lines in each category of biotherapeutics and summarise the factors influencing the choice of host cell lines used.